Surgical findings and technical knacks to performing living donor liver transplantation for hepatocellular carcinoma recurrence after carbon ion radiotherapy. Issue 8 (22nd August 2018) - Huang, Yu; Hidaka, Masaaki; Takatsuki, Mitsuhisa; Soyama, Akihiko; Adachi, Tomohiko; Ono, Shinichiro; Kugiyama, Tota; Hara, Takanobu; Okada, Satomi; Yoshimoto, Tomoko; Hamada, Takashi; Eguchi, Susumu
Abstract: Although carbon-ion radiotherapy (CIRT) has been reported to achieve good local control of hepatocellular carcinoma (HCC), liver transplantation is still required in patients with tumor recurrence. However, few cases of living donor liver transplantation (LDLT) after curative CIRT for HCC has been reported. It would be of great interest to ascertain the true situation of the irradiated region as well as to clarify the surgical points. We herein report the surgical findings and our experience along with technical difficulties and knacks concerning two cases of LDLT for HCC after CIRT. Both patients suffered tumor recurrence after curative CIRT for HCC. Severe adhesions were found between the irradiated region and the surrounding tissues, which resulted in surgical difficulties. Histological findings showed severe tissue fibrosis in the CIRT area. We should pay attention to adhesions in the irradiated area caused by CIRT including the vascular reconstruction during surgery.